If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -1t + -8 = 3t + -3 Reorder the terms: -8 + 5t + -1t = 3t + -3 Combine like terms: 5t + -1t = 4t -8 + 4t = 3t + -3 Reorder the terms: -8 + 4t = -3 + 3t Solving -8 + 4t = -3 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. -8 + 4t + -3t = -3 + 3t + -3t Combine like terms: 4t + -3t = 1t -8 + 1t = -3 + 3t + -3t Combine like terms: 3t + -3t = 0 -8 + 1t = -3 + 0 -8 + 1t = -3 Add '8' to each side of the equation. -8 + 8 + 1t = -3 + 8 Combine like terms: -8 + 8 = 0 0 + 1t = -3 + 8 1t = -3 + 8 Combine like terms: -3 + 8 = 5 1t = 5 Divide each side by '1'. t = 5 Simplifying t = 5
| 7(-8*-8*-8)-3= | | x=12+-5y | | 1/2h+1/3(h+6)=5/6h+2 | | 3.2/6.4 | | 8x33/8=3y-7 | | 3-(-4/5-2) | | 7k+6k=-13 | | x/p+x/a=5 | | 21/3+11/4x3 | | 5x+7=-3x+4 | | 4x+2y+3z=586 | | 3x+5/4=2x-2/4 | | 3x=18x-9 | | (4x-3)(3+4x)-2x(8x-1)=0 | | Z^2-9z=-20 | | 4x^2+4x^3= | | 2(4m+9)=6(3m+7) | | x=5x+10 | | 4x^2-8x^6-2x^3=0 | | y-15=x | | 3v-9=15+3v | | 2/4+1 | | 4(x+1)+2=-2 | | 55+.25sd=45+.35sd | | 10-3m=-47 | | f(x)=144 | | 5.4x7/18 | | 2(x-3)+x=-15 | | n5/31/5 | | 80-(4x+14)=4(x+3)+x | | 2x=-81 | | n-8.08=11.65 |